The computer-aided design and rapid prototyping fabrication of removable partial denture framework for occlusal rehabilitation: clinical report (Research, Society and Development, 2020)
The objective of this case report was to describe the clinical sequence for occlusal vertical dimension (OVD) recovering with the manufacture of removable partial dentures (RPD) produced by computer-aided design and rapid prototyping. The patient presented to the Dentistry Department of the Federal University of Rio Grande do Norte reporting dissatisfaction with the superior RPD. At clinical investigation, a fracture in the minor connector and support at the region of tooth 15 was observed, in addition to severe OVD loss. In this case, after obtaining correct OVD, four more sessions were necessary for RPD fabrication. In the first appointment, intraoral scanning was performed to generate STL files used for path of insertion determination in the CAD software. The need for a guide plane on tooth 15 was observed, thus a preparation guide was designed and 3Dprinted to aid axial tooth reduction. At the second visit, after mouth preparation, another intraoral scanning was performed to acquire virtual working models. The RPD framework was designed and 3D printed in a castable resin pattern and invested for cobalt-chromium alloy melting. In the third visit, clinical evaluation of the framework and teeth and artificial gingiva colors selection were performed. The articulated models were then 3D printed, enabling pre-fabricated teeth to be assembled and acrylized. On the fourth appointment, RPD was installed and the patient received routine instructions. In this sense, the use of CAD/CAM technologies presented as a valuable tool to enhance restoration of OVD by the manufacturing of RPD.